Maternal physical activity levels in early pregnancy and the risk of spinal deformity among preschoolers at age 4: findings from the Shanghai birth cohort study - Li, Xin; Zhou, Xuan; Liang, Juping; Huang, Zefan; Jin, Mengdie; Shen, Xiuhua; Wang, Xuanfang; Fu, Binbin; Chen, Peijie; Du, Qing (Frontiers in Pediatrics, 2025)
ObjectiveTo study the impact of maternal physical activity levels before and after birth on the risk of spinal deformity in preschool children.MethodsA cohort study of 760 preschoolers and their mothers tracked maternal physical activity levels during the prenatal period and the two years postnatally, as well as for two years after the child's birth, using standardized questionnaires at 6, 12, and 24 months. The risk of spinal deformity was assessed by the angle of trunk rotation (ATR) at the thoracic (T5), thoracic-lumbar (T12), and lumbar (L4) segments of the spine, with max values noted. An adjusted logistic regression model was used to explore the relationships between prenatal and postnatal physical activity levels and the risk of spinal deformity in preschoolers.ResultsIn 98 children (12.9%), ATRs were 3 or above, and 3 had ATRs of 5 at age 4. The duration of physical activity during early pregnancy (min/week) indicated a moderate risk of spinal deformity (with an ATR between 3 and 5) in children at age 4 (OR: 0.986, 95% CI: 0.976–1.001, P = 0.084). Exercising outdoors <1 h/day during 0–6 months reduced spinal deformity risk (3 ≤ ATRs < 5) compared to >1 h (OR = 0.525, 95% CI 0.301–0.917, p = 0.024). The risen risk of high ATR with long outdoor time was more significant when maternal blood calcium levels were low (OR=0.302, 95% CI 0.134–0.682; p = 0.004).ConclusionLong outdoor times (>1 h/day) in infants under 6 months may be associated with changes in trunk rotation angle or postural stress. Exercise during early pregnancy may relate to good spine development in children. Further studies are needed on physical activity's role in scoliosis prevention.